Modeling the light-induced electric potential difference (ΔΨ), the pH difference (ΔpH) and the proton motive force across the thylakoid membrane in C3 leaves - Lyu, Hui; Lazár, Dušan (Journal of theoretical biology, 2017)
A model was constructed which includes electron transport (linear and cyclic and Mehler type reaction) coupled to proton translocation, counter ion movement, ATP synthesis, and Calvin-Benson cycle. The focus is on modeling of the light-induced total electric potential difference (ΔΨ) which in this model originates from the bulk phase electric potential difference (ΔΨb), the localized electric potential difference (ΔΨc), as well as the surface electric potential difference (ΔΨs). The measured dual wavelength transmittance signal (ΔA515-560nm, electrochromic shift) was used as a proxy for experimental ΔΨ. The predictions for theoretical ΔΨ vary with assumed contribution of ΔΨs, which might imply that the measured ΔA515-560nm trace on a long time scale reflects the interplay of the ΔΨ components. Simulations also show that partitioning of proton motive force (pmf) to ΔΨb and ΔpH components is sensitive to the stoichiometric ratio of H+/ATP, energy barrier for ATP synthesis, ionic strength, buffer capacity and light intensity. Our model shows that high buffer capacity promotes the establishment of ΔΨb, while the formation of pHi minimum is not 'dissipated' but 'postponed' until it reaches the same level as that for low buffer capacity. Under physiologically optimal conditions, the output of the model shows that at steady state in light, the ΔpH component is the main contributor to pmf to drive ATP synthesis while a low ΔΨb persists energizing the membrane. Our model predicts 11mV as the resting electric potential difference across the thylakoid membrane in dark. We suggest that the model presented in this work can be integrated as a module into a more comprehensive model of oxygenic photosynthesis.
Keywords: listy rostlin; Membrane Potentials; pufry; protonmotorická síla; Buffers; Photosynthesis; Computer Simulation; uhlík; Ion movements; Hydrogen-Ion Concentration; transport elektronů; Models, Biological; protony; Thylakoids; světlo; koncentrace vodíkových iontů; membránové potenciály; Time Factors; Electron Transport; Electrochromic shift; tylakoidy; biologické modely; Protons; Carbon; Plant Leaves; časové faktory; počítačová simulace; Light; Proton-Motive Force